2016
DOI: 10.3390/atmos7030032
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Dew in a Cold Desert-Shrub Ecosystem and Its Abiotic Controls

Abstract: Abstract:The temporal dynamics of dew formation in cold desert-shrub ecosystems are still poorly understood. We examined dew and its abiotic controls in a shrubland in northwestern China with continuous eddy-covariance measurements of latent heat fluxes gathered over the growing-season of 2012. The dew amount was larger in mid-summer than in spring and autumn, but the dew duration was shorter in summer (from~10:00 p.m. to~6:30 a.m.) than in spring and autumn (from~8:30 p.m. to~7:30 a.m.). Dew occurred on 85% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 58 publications
5
21
0
Order By: Relevance
“…The in situ radiometric network from NEON has not been specifically designed to work in locations with high dew yield, and thus the data provide information on sites that span a continuum from exceptionally low dew frequencies to an almost nightly occurrence. However, former dew studies focusing on a single site have reported a similar RH threshold value below which dew has a low probability of forming: RH = 78 % in Wang et al (2017c) (204 nights in a semi-arid site in China using leaf wetness sensors) and RH = 75 % in Guo et al (2016) (166 nights in a cold desert in China using eddy-covariance data). Even if the linear relationship in Fig.…”
Section: Dew Frequency Duration and Yield Across Sitesmentioning
confidence: 91%
See 2 more Smart Citations
“…The in situ radiometric network from NEON has not been specifically designed to work in locations with high dew yield, and thus the data provide information on sites that span a continuum from exceptionally low dew frequencies to an almost nightly occurrence. However, former dew studies focusing on a single site have reported a similar RH threshold value below which dew has a low probability of forming: RH = 78 % in Wang et al (2017c) (204 nights in a semi-arid site in China using leaf wetness sensors) and RH = 75 % in Guo et al (2016) (166 nights in a cold desert in China using eddy-covariance data). Even if the linear relationship in Fig.…”
Section: Dew Frequency Duration and Yield Across Sitesmentioning
confidence: 91%
“…Dew formation is less well documented in forested sites than arid areas or croplands and/or grasslands, possibly because small inputs from dew are not likely to have a significant impact on these ecosystems or because their tall canopies are considered as a natural radiative barrier to dew formation. However, Hao et al (2012) reported a dew frequency of 73 % over 142 nights using eddy-covariance data in a hyper arid forest (canopy height 8-10 m, forest coverage of 50 %, and annual rainfall of 35 mm). The much higher dew frequency might be explained by the short canopy height, the low vegetation density, the presence of a river close to the area of study or sim- Figure 4.…”
Section: Dew Frequency Duration and Yield Across Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The dry and temperate grasslands have a dew duration of 3.4 ± 1.1 h (1 SD), and the forests have a duration of 4.5 ± 1.1 h (1 SD). A comparison with former studies is difficult because of the varying range of dew duration in the literature: from 1-4 h (Pan et al, 2010;Hao et al, 2012) to 4-6 h (Wang et al, 2017a) or above 6 h (Moro et al, 2009;Uclés et al, 2014;Guo et al, 2016) depending on the climatic conditions, canopy structure and measurement proto-col. Dew duration is positively affected by the relative humidity ( Fig. 4b), but it is also sensitive to a change in wind speed (see Sect.…”
Section: Dew Frequency Duration and Yield Across Sitesmentioning
confidence: 99%
“…Uclés et al (2015) demonstrated that dew events, daily amount of dew, and daily dew rates in winter for El Cautivo in Spain were greater than those in summer, whereas water vapor adsorption in summer was higher than that in winter. Guo et al (2016) stated that 85% of dew events in the Mu Us Desert of China occurred in the growing season. The amount of dew was higher in summer than that in spring or fall, whereas the duration of dew followed an opposite trend.…”
Section: Weather Conditionsmentioning
confidence: 99%